2010
DOI: 10.3892/ijmm_00000386
|View full text |Cite
|
Sign up to set email alerts
|

Decursin inhibits growth of human bladder and colon cancer cells via apoptosis, G1-phase cell cycle arrest and extracellular signal-regulated kinase activation

Abstract: Abstract. Decursin, a pyranocoumarin isolated from the KoreanAngelica gigas root, has demonstrated anti-cancer properties. In the present study, we found that decursin inhibited cell viability in cultured human urinary bladder cancer 235J cells and colon cancer HCT116 cells. The inhibited proliferation was due to apoptotic induction, because both cells treated with decursin dose-dependently showed a sub-G1 phase accumulation and an increased cytoplasmic DNA-histone complex. Cell death caused by decursin was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In general, the cell cycle arrest is a prestage that induces apoptosis. Previous reports have reported that decursin acts on the cell cycle and is involved in antitumor effects in prostate cancer, bladder cancer, and colorectal cancer [ 29 , 33 ]. In this study, decursin increased the number of cells in the G0/G1 phase and decreased in the S-phase on human osteosarcoma cell lines at 24 h. Decursin also acted on cyclin D1 and CDK6 that arrests the cell cycle in G0/G1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the cell cycle arrest is a prestage that induces apoptosis. Previous reports have reported that decursin acts on the cell cycle and is involved in antitumor effects in prostate cancer, bladder cancer, and colorectal cancer [ 29 , 33 ]. In this study, decursin increased the number of cells in the G0/G1 phase and decreased in the S-phase on human osteosarcoma cell lines at 24 h. Decursin also acted on cyclin D1 and CDK6 that arrests the cell cycle in G0/G1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support the conclusion that the fat-soluble polyphenols in MH-30 contributed to inhibition melanoma growth. There are many reports that decursin exhibits anticancer activity by inhibiting the Wnt/βcatenin pathway, inducing cell cycle arrest and apoptosis, and inhibiting VEGF-induced angiogenesis, and also by inhibiting metastasis by targeting MMP-9 activity (53)(54)(55)(56). In addition, MH-30 showed a synergistic effect in combination with cisplatin on melanoma growth inhibition in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Decursin is isolated from the root of Angelica Gigas, and it has been shown to mediate cancer formation, angiogenesis, and inflammation [238]. It can effectively suppress tumor growth by inducing apoptosis via G1-phase cell cycle arrest and decreasing proliferation and angiogenesis through VEGF receptor inactivation and protein kinase C activation [239][240][241][242][243][244][245][246]. Meanwhile, decursin has been demonstrated to block COX-2 expression in the inflammatory bowel disease model as well as inhibiting PI3K, ERK, and NF-κB activation in the in vitro cancer cell line studies [247][248][249][250].…”
Section: Nonsteroidal Compounds: Decursinmentioning
confidence: 99%